2020
DOI: 10.3390/microorganisms8060918
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Chlamydia trachomatis and Waddlia chondrophila Antibodies in Women with Tubal Factor Infertility

Abstract: Waddlia chondrophila is an emerging intracellular pathogen belonging to the order of Chlamydiales, and was previously associated with adverse pregnancy outcomes, as well as tubal factor infertility (TFI). In this study, we investigate the link between both W. chondrophila and Chlamydia trachomatis IgG seropositivity and TFI. Antibodies against both bacteria were measured in 890 serum samples of women visiting a fertility clinic. After a hysterosalpingography and/or laparoscopy, they were classified as either T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The extensive use of a single dose of AZT for uncomplicated chlamydia infections is questionable [ 3 ], whereas the efficacy of conventional treatment is threatened by the continuous rise of AMR and might become limited [ 4 , 5 , 6 ]. Treatment failure or even the lack of treatment can be associated with serious consequences such as ectopic pregnancy and tubal infertility [ 7 ]. In the search for novel tools to tackle AMR, natural substances with multi-targeted pharmacological properties have emerged as possible alternatives to antibiotics [ 8 ], including for the treatment of C. trachomatis infections [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive use of a single dose of AZT for uncomplicated chlamydia infections is questionable [ 3 ], whereas the efficacy of conventional treatment is threatened by the continuous rise of AMR and might become limited [ 4 , 5 , 6 ]. Treatment failure or even the lack of treatment can be associated with serious consequences such as ectopic pregnancy and tubal infertility [ 7 ]. In the search for novel tools to tackle AMR, natural substances with multi-targeted pharmacological properties have emerged as possible alternatives to antibiotics [ 8 ], including for the treatment of C. trachomatis infections [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 27 According to Hoenderboom et al, 22 CT positivity represents a fourfold higher risk for TFI. In the study performed by van Dooremalen et al, 26 it is observed that CT antibodies were significantly more common among the group with TFI compared to the group without it, respectively 41.9% and 9.6%. 26 Additionally, Rawre et al 11 supported this correlation, once they observed that 56 out of the 75 women with TFI had had CT infection.…”
Section: Discussionmentioning
confidence: 88%
“…In the study performed by van Dooremalen et al, 26 it is observed that CT antibodies were significantly more common among the group with TFI compared to the group without it, respectively 41.9% and 9.6%. 26 Additionally, Rawre et al 11 supported this correlation, once they observed that 56 out of the 75 women with TFI had had CT infection. Nevertheless, the mechanism behind this interconnection is still unclear.…”
Section: Discussionmentioning
confidence: 88%
“…Compared with women whose chlamydia testing status was negative, women whose test was positive had an 85% increased risk of infertility ( 40 ). In a study screening of chlamydia antibodies in 890 women visiting fertility clinics, chlamydia antibodies were present significantly more often in tubal factor infertility ( 27 ). However, those studies were based on qualitative data of chlamydial infection and not quantitative.…”
Section: Discussionmentioning
confidence: 99%